PENGARUH LEVERAGE DAN MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA - Sari, Septiana Ratna (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to test the influence of leverage and good corporate governance mechanism to theearnings management. The subject of the research is the manufacturing companies which are listed in theIndonesia Stock Exchange from 2009 to 2011. The samples selection is performed by using purposive samplingmethod, it selects samples by applying certain criteria which in appropriate with what the researcher wants, asmuch as 174 observation objects of 58 companies during 2009 â 2011 are obtained by using the samples selectionmethods. The multiple regressions analysis is used as the analysis technique in this research. The classicassumption test is conducted before the data is processed. This research applies leverage and good corporategovernance mechanism with the proxy of managerial ownership, institutional ownership, board ofcommissioners, independent commissioners, auditing committee as independent variables, and earningsmanagement as dependent variable. The result indicates that there is no heteroscedaticity, autocorrelation andmulticolinearity. The result of partial test indicates that the leverage has negative effect to the earningsmanagement. The result of good corporate governance partial test to the earnings management with the proxy ofinstitutional ownership, the board of commissioners and the auditing committee has positive influence to theearnings management. The result of good corporate governance partial test to the earnings management with theproxy of independent commissioners has negative influence to the earnings management.Keywords: Leverage, Good Governance Governance, Earnings Management